Evaluating Snake Density Using Passive Integrated Transponder (PIT) Telemetry and Spatial Capture–Recapture Analyses for Linear Habitats - Leuenberger, Wendy; Davis, Allison G; Mckenzie, Jennifer M; Drayer, Andrea N; Price, Steven J (Journal of herpetology, 2019)
Many snake species are elusive and difficult to study in field settings. As such, little is known about their population ecology despite conservation needs for many species. Advances in field techniques and statistical methods can improve our understanding of snake ecology. We used passive integrated transponder (PIT) telemetry to track Nerodia sipedon (Northern Watersnakes, n = 94) and Regina septemvittata (Queensnakes, n = 119) in six low-order streams in central Kentucky, USA from June to October 2016. We assessed snake density, spatial scale of detection, and detection probability using PIT tag relocations and spatial capture–recapture methods for linear habitats. Specifically, we modeled population density as a function of individual stream and land cover type, spatial scale of detection as a function of sex, and detection probability as a function of sex and time-varying covariates. Individual streams were a better predictor of snake density than land cover type; density estimates ranged from 6 ± 3 N. sipedon/km (mean ± standard error) to 107 ± 17 N. sipedon/km and 6 ± 5 R. septemvittata/km to 63 ± 10 R. septemvittata/km. Female R. septemvittata had a larger spatial scale of detection (55 ± 4 m) than male R. septemvittata snakes (40 ± 4 m). Spatial scale of detection did not differ between sexes for N. sipedon (females: 40 ± 4 m; males: 35 ± 3 m). The combination of PIT telemetry and spatial capture–recapture analyses can effectively estimate population densities and other population parameters for snakes and other reptiles and amphibians associated with linear habitats.